Identifying, categorizing and ranking performance indicators of schools using Q method - Seyed Mahmoud Jalilian; Shahnaz Naibzadeh; seyyed hasan hataminasab; seyed ali almodaresi (مدیریت و چشم انداز آموزش)
The aim of the current research is to identify, categorize, and rank school performance indicators using the Q method. The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of implementation, and interpretive paradigm. This research was done in two steps; the research strategy in the first step is qualitative content analysis, and the statistical population of the research includes 24 people from four groups of parents, managers and employees of girls' high school, teachers and also the officials of the Yazd City Education Organization, by and targeted sampling; and the sample size continued up to theoretical saturation, and performance indicators were extracted from the semi-structured interview. In the second step of this research, using Q-axis factor analysis, the mental typology of 33 parents was investigated using a questionnaire and in-the-field. Content analysis was used in qualitative data analysis, and SPSS software and Q method were used in quantitative data analysis. The findings of the research have led to the achievement of seven different types of minds, indicating heterogeneity and significant differences in the views of parents regarding performance criteria; a difference that invited the managers of this school to segment the market based on understanding the desires and needs of the target audience with different mentalities. and improves the insight of managers of this industry regarding capital allocation by looking from outside to inside and emphasizing on audience-oriented evaluation system. Extended abstract Introduction The Education is the main educational institution and one of the largest social organizations, which plays a fundamental and important role in realizing the cultural, educational, social and economic goals of society, and the level of development of any society depends on its quality level (Andam & Taheri, 2019). The goal of every educational system is the all-round development and improvement of students in cognitive, emotional, psychological, and motor fields. As the future makers of every country, students form an important group of people in society (Vrghese & Rathnasabapathy, 2020) and therefore one of the most important concerns of educational institutions today is success in education, which means that every educational institution is efficient when its audience are academically in a favorable condition (Muhonen & et al, 2018) and their subjective assessment of the institution's performance should be positive and lead to continued communication and receiving services from it (Karababa, 2020). Considering the significant importance of school in the growth and upbringing of children and adolescents, it is important to study their interest and enthusiasm for school and the factors related to enthusiasm for school (Nouri, 2017). One of the important factors affecting student enthusiasm is school performance, which can have a significant impact on the selection process of students and parents (Tuominen et al, 2020.( The main question that this research was conducted in order to answer is: what are the evaluation criteria of parents of students of Sama Girls' High School in Yazd in the second grade of education, which provides a good basis for judging the performance of the school in terms of more than one year of contact with the school? And how is the mental typology of mothers as one of the most important effective roles in the decision-making process for the school of female students? Theoretical Framework School performance Due to the intensification of competition between schools in recent years, schools are inclined towards improving their performance and have taken into consideration the identifying performance indicators and improving them from the path of competent and scientific measurement as an important part of the measures underlying the growth and excellence of the education system of the country. In fact, the main philosophy of performance measurement is to be aware of the level of performance that the organization is in, and to determine in which departments and steps things are going well, so that the foundations of success can be strengthened based on that. In addition, by revealing the parts and steps in which things are not well done and followed up, appropriate corrective measures can be designed and implemented (Ghaffari et al, 2013). Oladhamzehzadeh et al, (2024) investigated the design of an educational model based on identity development with an Iranian-Islamic approach for elementary school students. 20 experts from the academic community and specialists have been questioned to investigate the performance of students in the qualitative section; in the quantitative part of this research, 217 principals, assistants, teachers, and staff of elementary schools in five cities of Tehran have been considered, and the identified factors have been extracted in the form of 9 dimensions and 61 components. In this research, the dimensions of the educational model based on the development of students' identity with the Iranian-Islamic approach includes educational goals and content, teaching and learning methods, instructors and teachers, cultural factors, social factors, psychological factors, media, educational factors, and family factors. Based on the results of quantitative analysis, all dimensions and components of the model were valid and the model has a good fit. Ong et al, (2021) investigated performance evaluation in one of the public secondary schools in Malaysia. The results showed that performance evaluation is important for tracking teachers' productivity, their career development, providing a clearer career path, and helping teachers to improve job quality, provided that performance evaluation is carried on based on accurate criteria and fair evaluation and with cooperation and mutual communication between the manager and the teacher. Research methodology The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of implementation, and interpretive paradigm. This research was done in two steps; the research strategy in the first step is qualitative content analysis, and the statistical population of the research includes 24 people from four groups of parents, managers and employees of girls' high school, teachers and also the officials of the Yazd City Education Organization, by and targeted sampling; and the sample size continued up to theoretical saturation, and performance indicators were extracted from the semi-structured interview. In the second step of this research, using Q-axis factor analysis, the mental typology of 33 parents was investigated using a questionnaire and in-the-field. Research findings Content analysis was used in qualitative data analysis, and SPSS software and Q method were used in quantitative data analysis. The findings of the research have led to the achievement of seven different types of minds, indicating heterogeneity and significant differences in the views of parents regarding performance criteria; a difference that invited the managers of this school to segment the market based on understanding the desires and needs of the target audience with different mentalities. and improves the insight of managers of this industry regarding capital allocation by looking from outside to inside and emphasizing on audience-oriented evaluation system. Conclusion The current research was conducted with the aim of identifying, categorizing, and ranking school performance indicators using the Q method. The results of this research are in agreement with the results of Oladhamzehzadeh et al, (2024), Sori et al, (2023), Narimani et al, (2021), Ong et al, (2021), Taghipur Zahir et al, (2019), Moradi & AminBidakhti (2018), Ghaffari & Shirvani (2016), Khan et al, (2014), Whitford (2013), Nazari et al, (2013), and Abdulahi (2007). Ong et al, (2021) showed that performance evaluation is important for tracking teachers' productivity, their career development, providing a clearer career path, and helping teachers to improve job quality, provided that performance evaluation is based on accurate criteria and fair and collaborative evaluation and mutual communication between the manager and the teacher. According to the results of the research, it is suggested to take into account the difference in the mothers' views on a continuous and periodic basis to receive the views of the parents regarding the performance of the school, and not only to focus on improving the performance indicators identified from the perspective of the four groups in this research, but also they also consider the students' views and opinions and provide the basis for achieving a comprehensive performance evaluation system that can provide the appropriate tool and ruler for the school in order to achieve the high goals.